Manajemen Pendidikan Akhlak Perspektif Al-Ghazali di Pondok Pesantren Ashhabul Yamin Lasi Tuo - Athari Naufal; Wedra Aprison; Salmi Wati (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2024)
Among the students there are still those who have a lot of religious knowledge but are unable to apply it in the form of respect and respect for others. This condition shows that the moral or character education of some of the students at the Islamic boarding school is still weak. Therefore, efforts are needed to improve the quality of moral education for students so that they can behave politely, friendly and respect each other. Therefore, the aim of this research is to describe and analyze the management of moral education from Al-Ghazali's perspective based on the book Ihya Ulumuddin in class 5 of the Ashhabul Yamin Lasi Tuo Islamic Boarding School along with the obstacles faced. This research use desciptive qualitative approach. The moral book teacher from Al-Ghazali's perspective is the main informant for the research and other supporting informants are the boarding school leaders, homeroom teachers and students. Researchers collected data using observation, interview and documentation techniques. The analysis technique used by the author is data collection, reduction, presentation and drawing conclusions. Researchers used data triangulation to test the validity of the data. According to researchers, moral education management from Al-Ghazali's perspective is in accordance with what it should be, but more familiarization is needed as a form of evaluation of the implementation of moral education management from Al-Ghazali's perspective.